QR Code Assisted Pop-Up Book for Grade Two Elementary Schools - Nia Pratamanita Ardika; I Gede Margunayasa; Kadek Yudiana (Universitas Pendidikan Ganesha, 2022)
The implementation of this research is based on the limited material available in student books and the absence of support for qr-code-assisted pop-up books, so it is necessary to develop learning media at the elementary school level. The purpose of this study was to analyze the validity and practicality of the qr-code-assisted pop-up book on theme 8 sub-theme 2 for grade II elementary school. This research is a type of development research using the ADDIE model. The test subjects in this study were 3 material experts, 2 media experts, 2 practitioner experts and 10 students. The questionnaire method was used as a data collection method in this study. The instrument used is a rating scale with a scale of five. The data was then analyzed using the mean formula to calculate the average validity and practicality score of the pop-up book media. The average value of the validity of the pop-up book media obtained is 4.85 with a very good level in accordance with the findings. While the average practicality of the pop-up book media obtained is 4.86 which is at a very good level. Based on this analysis, it can be concluded that the pop-up book media developed with the help of qr-code on theme 8 sub-theme 2 is valid and practical for use in learning in grade II elementary school.